Indian gas supply : elixir for growth or priced out of reach? - Hansen, C (Oxford Institute for Energy Studies, 2005)
The continued development of new gas supplies in western India will have a significant impact on electricity markets and new investment in power, fertiliser and other industrial sectors. However, rising international oil and gas prices and the preponderance of gas contracts benchmarked to crude prices have increased prices of imported gas supplies and may scupper demand growth. This article surveys the gas supply situation in the sub-continent and examines the emerging LNG regassification market in western India, and how electricity and industrial companies may respond.